2011
DOI: 10.3168/jds.2010-3908
|View full text |Cite
|
Sign up to set email alerts
|

Corn grain and liquid feed as nonfiber carbohydrate sources in diets for lactating dairy cows

Abstract: Interactions of sources and processing methods for nonstructural carbohydrates may affect the efficiency of animal production. Five rumen-cannulated cows in late lactation were placed in a 5 × 5 Latin square design and fed experimental diets for 2 wk. In the production trial, 54 cows were fed the experimental diets for 12 wk beginning at d 60 in milk. Diets contained 24% corn silage and 22% hay, averaging 20% alfalfa and 2% grass but being adjusted as needed to maintain dietary concentrations of 36% neutral de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Unfortunately, those researchers did not show that data, nor did they accurately quantify the degree of sorting (based on actual and predicted amounts of particles consumed). Molasses, or LF containing a high proportion of molasses, may be more effective than adding water at decreasing sorting for rations lower in DM content (Eastridge et al, 2011). In previous research, sorting against the longest ration particles was increased, rather than decreased, when water was added to a TMR with a DM content <60% and containing no dry forage (Miller-Cushon and DeVries, 2009;Felton and DeVries, 2010).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Unfortunately, those researchers did not show that data, nor did they accurately quantify the degree of sorting (based on actual and predicted amounts of particles consumed). Molasses, or LF containing a high proportion of molasses, may be more effective than adding water at decreasing sorting for rations lower in DM content (Eastridge et al, 2011). In previous research, sorting against the longest ration particles was increased, rather than decreased, when water was added to a TMR with a DM content <60% and containing no dry forage (Miller-Cushon and DeVries, 2009;Felton and DeVries, 2010).…”
Section: Discussionmentioning
confidence: 92%
“…The addition of the LF did change the DM particle distribution of the ration, resulting in a lesser proportion of short particles and a greater proportion of long, medium, and fine particles. One would predict that the adhesiveness of the molasses-based LF supplement would help bind the short ration particles to the longer ration particles, as seen by Oelker et al (2009) for corn-silage based rations and Eastridge et al (2011) for a TMR containing finely ground corn grain. It is worthwhile to note in the current study that more variability was observed in the proportions of the long and medium particles in the LF diet, suggesting that some inconsistency may have occurred in how well the LF was mixed through the TMR on a daily basis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Golchin-Gelehdooni et al (2011), diets with reducing particle size decrease the filling effects of forage and increase ruminal passage rate of the nutrients through the rumen, a fact that possibly contributed to a reduction in the nutrient digestibility (Table 3). Moreover, the passage and degradation rates are affected by chemical and physical composition, feed processing (Eastridge et al 2011), with elevated fractions of fast rumen digestion reducing the retention time of the feed in the rumen. Related to these factors, the rumen ambient may have been impaired by the greater proportion of fermentable carbohydrates present in the liquid residue of cassava, thereby possibly reducing the rumen pH and the nutrient digestibility.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of diference between grinding and laking could be due to low grain inclusion rate and minimal diference in the particle size as barley was coarsely ground. In contrast, Eastridge et al [54] reported that the inely ground corn decreased milk urea nitrogen content compared with coarsely ground corn, suggesting that inely ground corn provided more fermentable starch in the rumen, thus possibly improved bacterial capture of the nitrogen. However, the results on dry mater intake, milk production of lactating dairy cows by feeding steam-laked corn versus ground corn are inconsistent [55][56][57].…”
Section: Steam-laking Versus Rolling or Grindingmentioning
confidence: 93%